2020
DOI: 10.3390/ijerph17217716
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Dental Emergency Services in Cluj-Napoca Metropolitan Area: A Cross-Sectional Study

Abstract: This study aimed to assess dental care needs in Cluj region during the State of Emergency, declared due to the COVID-19 pandemic, compared to the same period of the year 2019. A descriptive retrospective analysis was conducted, which retrieved patients seeking emergency dental services at the Emergency Department of County General Hospital and “Iuliu Hațieganu” University of Medicine and Pharmacy, Cluj-Napoca, Romania, the only dental service available in April 2020. Recorded data cover the month of April 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 23 publications
(19 reference statements)
2
16
0
4
Order By: Relevance
“…Severe dental pain from pulpal inflammation (% 15.96) and abscess/localized pain and swelling (% 12.06) were the most frequent reason for child patients’ urgent dental care attendance during the pandemic period, as well as during non-pandemic period, whereas visits regarding dental trauma were low. Our findings are in-line with previous researchers reporting dental pain from pulpal inflammation, abscess, or swelling as the most common reason for patients seeking treatment [ 9 , 10 , 17 19 ]. Although pulpectomy was situated as management of signs and symptoms related to dental pain and abscess/swelling during the non-pandemic period, extraction was preferred to refrain from the high risk of aerosols (Table 3 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Severe dental pain from pulpal inflammation (% 15.96) and abscess/localized pain and swelling (% 12.06) were the most frequent reason for child patients’ urgent dental care attendance during the pandemic period, as well as during non-pandemic period, whereas visits regarding dental trauma were low. Our findings are in-line with previous researchers reporting dental pain from pulpal inflammation, abscess, or swelling as the most common reason for patients seeking treatment [ 9 , 10 , 17 19 ]. Although pulpectomy was situated as management of signs and symptoms related to dental pain and abscess/swelling during the non-pandemic period, extraction was preferred to refrain from the high risk of aerosols (Table 3 ).…”
Section: Discussionsupporting
confidence: 93%
“…Viral particles as well as small infected droplets in the air may cause through long-distance transmission between the patient and the dental staff [5,8]. These potential transmission routes resulted in patient anxiety, which affected the dental attendances, especially in emergency clinics [9][10][11][12]. On 16 March 2020, American Dental Association (ADA) released a recommendation to postpone elective procedures as a measure to prevent the spread of COVID-19 [13].…”
Section: Introductionmentioning
confidence: 99%
“…Related patient attitudes and behavior could also be found in other countries; our study supports the findings that COVID-19 significantly impacted peoples’ dental care-seeking behavior in Cluj-Napoca, Romania [ 16 , 23 , 24 , 25 ].…”
Section: Discussionsupporting
confidence: 87%
“…In Romania, patients’ fear of exposure to SARS-CoV-2 has led to a decreased addressability in dental offices during the state of emergency period, even in case of emergency treatments [ 16 ]. This trend was also noted in the months following the state of emergency.…”
Section: Introductionmentioning
confidence: 99%
“…The only research in Romania focusing on dental emergency services during COVID-19 pandemic was conducted by Petrescu et al [ 20 ] in one of the largest counties of Romania. The paper showed that the number of patients decreased, so, besides the economic and social life of the population, the pandemic impacted the use of medical care services, with important consequences during the post-lockdown period (an increased number of dental problems and patients).…”
Section: Introductionmentioning
confidence: 99%